Changes in quality of life of early-stage lung cancer patients undergoing sublobar resection: a systematic review - Magouliotis, Dimitrios E.; Cioffi, Ugo; Minervini, Fabrizio; Lampridis, Savvas; Guttadauro, Angelo; Scarci, Marco (Frontiers in Surgery, 2025)
ObjectiveThis systematic review aimed to evaluate the impact of sublobar resection (SLR) on the quality of life (QoL) of patients with early-stage non-small cell lung cancer (NSCLC). Specifically, it compared outcomes between sublobar resection, lobectomy, and stereotactic body radiation therapy (SBRT).MethodsA literature search was conducted across PubMed and Scopus, identifying studies published from 2010 to 2024 that reported QOL outcomes in early-stage NSCLC patients treated with lobectomy, SLR, or SBRT. Inclusion criteria were studies with more than 10 patients, written in English, and using validated QoL metrics. Data on demographics, interventions, QoL tools, and findings were extracted, and study quality was assessed using the Newcastle-Ottawa Scale and the ROBINS-I tool.ResultsFive studies involving 1,149 patients from six countries met the inclusion criteria. QoL outcomes consistently favored SLR over lobectomy in domains such as physical and respiratory function, with SLR patients experiencing faster recovery and fewer complications. Minimally invasive techniques, such as video-assisted thoracoscopic surgery (VATS), further enhanced these outcomes. SBRT demonstrated stable QOL post-treatment but lacked the long-term physical recovery benefits observed with SLR. Commonly employed QoL tools included the EORTC QLQ-C30, Leicester Cough Questionnaire, and NSCLC-PQOL, each capturing distinct dimensions of patient QoL status.ConclusionSublobar resection provides significant QoL benefits for selected early-stage NSCLC patients compared to lobectomy, particularly in respiratory health and recovery endpoints. These findings highlight the value of personalized surgical approaches and the need for further research on optimizing QoL in NSCLC management.